2016
DOI: 10.1093/geronb/gbw091
|View full text |Cite
|
Sign up to set email alerts
|

Job Strain as a Risk Factor for Incident Diabetes Mellitus in Middle and Older Age U.S. Workers

Abstract: High strain and passive occupations which represent low control over work are associated with increased risk of diabetes incidence among older workers. More research is required to better understand how psychosocial work factors impact health in aging workers. Further, research should continue to explore gender differences in effects of job strain on diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Since the findings from previous studies on work-related stress on the risk of T2DM were inconsistent and inconclusive, it can be assumed that the etiology of T2DM is multifactorial and work-related stress may contribute to, or increase, the risk of T2DM development [21]. Similarly, a study in the US on working adults 50 years old and older found that high work strain and passive occupations were associated with an increased risk of T2DM [22]. Job stress was associated with a lower risk of T2DM in non-obese men but not in obese individuals, and an inverse relationship with a higher risk of T2DM was found in obese women but not in non-obese women [23].…”
Section: Discussionmentioning
confidence: 99%
“…Since the findings from previous studies on work-related stress on the risk of T2DM were inconsistent and inconclusive, it can be assumed that the etiology of T2DM is multifactorial and work-related stress may contribute to, or increase, the risk of T2DM development [21]. Similarly, a study in the US on working adults 50 years old and older found that high work strain and passive occupations were associated with an increased risk of T2DM [22]. Job stress was associated with a lower risk of T2DM in non-obese men but not in obese individuals, and an inverse relationship with a higher risk of T2DM was found in obese women but not in non-obese women [23].…”
Section: Discussionmentioning
confidence: 99%
“…High strain jobs have been repeatedly associated with adverse health outcomes, such as cardiac autonomic imbalance, as suggested by Heart Rate Variability, hypertension, or metabolic syndrome. [ 33 , 34 , 35 , 36 , 37 ]. In our study population, we observed an effect of job strain on perceived well-being, but not on CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…and other countries . Job strain, a combination of high levels of job demands and low levels of control over one's work, is a risk factor for adverse health effects, including cardiovascular disease . The job strain (job demands and control) model was introduced in 1979 by Robert Karasek and explains how the risk of adverse health outcomes, including cardiovascular disease and its risk factors, can be increased by high work demands and low job control or job decision latitude.…”
Section: Introductionmentioning
confidence: 99%